Evaluasi User Interface Pada Sistem Informasi E-Kinerja Kabupaten Muara Enim Dengan Metode System Usability Scale (SUS) - Saputra, Yudi; Suyanto; Sopiah, Nyimas; Wardani, Kiky Rizky Nova (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The benefits of evaluation are improving and achieving a goal and identifying problems with an information system by users. Many agencies use information systems as the backbone for disseminating information. This condition also occurs in the Muara Enim Regency Government, which uses the e-kinerja information system as a forum for distributing information on assessing the performance of State Civil Apparatus within the Muara Enim Regency Government. So the existence of an e-performance information system is very important because it concerns the performance of ASN itself. For this reason, this research will carry out an evaluation to find out or see the views of users regarding the form and appearance of the Muara Enim Regency e-performance information system. In carrying out this evaluation, the method used is the System Usability Scale (SUS) method. The results of this research will be in the form of statistical data relating to users' views of the Muara Enim Regency e-performance information system.